2010
DOI: 10.19030/iber.v9i3.532
|View full text |Cite
|
Sign up to set email alerts
|

The Theoretical Impact Of The Listing Of Syariah-Approved Stocks On Stock Price And Trading Volume

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
(15 reference statements)
3
16
1
1
Order By: Relevance
“…inclusion of new stocks in the FBM Shariah index. The findings are inconsistent with Sadeghi (2008) and Mcgowan and Muhammad (2010) that report the positive impact on stock prices when the stocks are announced as Shariah compliant stocks. The possible reasons could be due to insensitivity to market towards information on new Shariah compliant stocks.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…inclusion of new stocks in the FBM Shariah index. The findings are inconsistent with Sadeghi (2008) and Mcgowan and Muhammad (2010) that report the positive impact on stock prices when the stocks are announced as Shariah compliant stocks. The possible reasons could be due to insensitivity to market towards information on new Shariah compliant stocks.…”
Section: Resultscontrasting
confidence: 85%
“…This indicates that the investors react quickly to the deletion announcement by switching their investment in the other Shariah compliant stocks within 3 days before and after the announcement. The results are consistent with Sadeghi (2008), Mcgowan and Muhammad (2010) and Bacha and Abdullah (2001) who find that stocks that are no longer listed as Shariah compliant would experience a decrease in share price. This is consistent with the price pressure hypothesis that there will be a selling pressure in the market which leads to pushing the stock price down.…”
Section: = -supporting
confidence: 89%
“…It is consistent with finding found by [8] which found that stocks that are no longer listed as Shariah-compliant would experience a decrease in share price. Similarly, [9] also found that deletions as Shariah-compliant stocks experience negative impact. As mentioned by SC the investors are given six months from the effective date of the updated list (29 November 2013) to dispose of such securities.…”
Section: B Methodologymentioning
confidence: 88%
“…Similarly, an event such as the announcement of the Shariah-compliant list would affect an investor"s buying, holding or selling decision as a Shariah-compliant investor would be compelled to sell shares that are no longer listed as Shariah-compliant and substitute them with Shariah-compliant stocks. Therefore stocks that are no longer listed as Shariah-compliant would experience a decrease in share price and thus the stock returns as Shariah-compliant investors would be required to sell and invest in the other Shariah-compliant stocks that are available [9]- [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers (Abbes, 2012) have also argued that the difference in performance between the two types of stocks should be minimal and some have argued that conventional stocks should outperform the Islamic stocks (McGowan & Junaina, 2010). However, only limited research has been undertaken to date that relate to conventional and Islamic stocks using comparative areas of sectorial/industry, market capitalisation, price earnings ratio, market to book value ratio, debt to equity, and returns.…”
Section: Introductionmentioning
confidence: 99%